Effects of purple flour supplementation on the fermentation kinetics, apparent viscosity, and sensory acceptance in goat milk yogurt - Nathalia Brizack Monteiro; Katherine Gutierrez Alzate; Madian Johel Galo Salgado; Jose Givanildo da Silva; Iuri Lima dos Santos Rosario; Marion Pereira da Costa (Journal of Agriculture and Food Research, 2025)
This study evaluates the impact of purple flours (açaí, beetroot, and hibiscus) on goat milk yogurt's fermentation kinetics, apparent viscosity, and sensory acceptance. The experiment assessed how these purple flours, rich in anthocyanins, dietary fibers, and bioactive compounds, influence key fermentation parameters, including lactic acid bacteria (LAB) growth, acidification rate (pH), and apparent viscosity. Sensory acceptance was also analyzed immediately after the yogurts were manufactured. The results indicate that beetroot and hibiscus flour significantly enhanced LAB growth, reaching maximum cell concentrations of 13.2 and 13.3 log CFU/g, respectively. Hibiscus flour accelerated acidification, achieving a final pH of 4.5, while beetroot flour yielded the highest apparent viscosity (187.3 mPa s). Sensory analysis revealed that although these functional ingredients improved texture and visual appeal, hibiscus and beetroot flours introduced earthy and acidic notes that slightly reduced overall acceptability compared to the control and açaí flour formulations. These findings suggest that incorporating beetroot and hibiscus flours into goat milk yogurt enhances fermentation efficiency and texture, with potential applications in developing nutrient-enriched functional dairy products. However, further research is needed to optimize formulation ratios and balance textural improvements and flavor acceptance.